Основы системы музыкaльного обрaзовaния в Кaзaхстaне: исторический aспект - Mukasheva, A. (Journal of Educational Sciences, 2017)
This article describes the history of formation and development of music education in Kazakhstan. Based on historical data, the author presented the main aspects of the development of music education, since music schools-third graders from the Conservatory named after Kurmangazy. Also, in the article are asked the questions of professional training in music schools. In particular, it is noted that the system of mass musical education, a significant place belongs to the children music schools, which are associated with additional education. Citing the example that in Kazakhstan there are two types of music schools: children’s music school-seven years (elementary music education) and average eleven-year special music school (the initial stage in the preparation of professional musicians and experts in music). It is argued that music education at music school focused on mastery of a specific set of knowledge, skills and abilities required for the performance of music or any other active musical activities, at the same time, it includes the development of playing a musical instrument, ear training through special exercises, the acquisition of some theoretical and historical knowledge about music and musical culture of different countries. Key words: musical education, musical culture, music school, music career, music-making.